Effectiveness and safety of topical amphotericin B in 30% dimethyl sulfoxide cream versus 30% dimethyl sulfoxide cream for nondermatophyte onychomycosis treatment: A pilot study - Charussri Leeyaphan (2022)
Background: Although topical amphotericin B cream is effective for the treatment of nondermatophyte mold onychomycosis in vitro, studies of its effectiveness and safety in vivo are limited. Objectives: We studied the effectiveness and safety of topical 0.3% amphotericin B in 30% dimethyl sulfoxide cream (amphotericin B cream) in nondermatophyte mold onychomycosis using the vehicle cream 30% dimethyl sulfoxide cream as control. Methods: This randomized controlled study was conducted between January 2019 and November 2020. Patients diagnosed with nondermatophyte mold onychomycosis were randomly divided into two groups of ten patients each: one treated with amphotericin B cream and the other with the vehicle cream. Clinical and mycological cure as well as safety were evaluated. Results: Ten patients each treated with amphotericin B cream and the vehicle cream were included in the study, but only nine patients in the vehicle cream group were available for follow up. All the 19 evaluable patients had distal lateral subungual onychomycosis and the great toenails were affected in 18 (94.7%) of these. Mycological cure was achieved in 8 (80%) patients treated with amphotericin B cream and in 4 (44.4%) patients using the control (vehicle) cream. Clinical cure was achieved in 7 (70%) patients treated with amphotericin B cream, but only in 2 (22.2%) patients on the control cream. No adverse events were observed. Limitations: The small sample size and the fact that PCR fungal identification that provides accurate identification of fungal species was not performed are limitations of our study. Conclusion: Topical amphotericin B cream was both very effective and safe in the treatment nondermatophyte mold onychomycosis. The control (vehicle) cream containing 30% dimethyl sulfoxide also demonstrated some antifungal activity.